Best Answer

8m + (4n - 6m) + 9n =

8m + 4n - 6m + 9n =

(8m - 6m) + (4n + 9n) =

2m + 13n

More answers

Lvl 3

You can only simplify sorry not solve.

8m+4nā6m+9n

=8m+4n+ā6m+9n

Combine Like Terms:

=8m+4n+ā6m+9n

=(8m+ā6m)+(4n+9n)

=2m+13n

Q: What is 8m plus 4n-6m plus 9n?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-5 plus 9n plus 6 is 1 plus 9n.

2+3n+2+9n would equal 4+12n after adding all like numbers.

it equals -4n

9n-2=7n+50 7n+9n=50+2 16n=52 n= 3.25

n - 10 + 9n - 3 = 10n - 13

Related questions

-5 plus 9n plus 6 is 1 plus 9n.

(8m - 3n)^2 I assume you mean 'squared' , when you write 'square 2'. Because means raising to the power of '2'. Whereas 'cubing' means raising to the power of '3'. To answer (8m - 3n)(8m - 3n( = 64m^2 - 24mn - 24 mn + 9n^2 = 64m^2 - 48 mn + 9n^2 Done!!!!

9n + n = 10n

9n + 18 = 81 9n = 63 n = 7

15m + 4n - 5m + 9n = 10m + 13n

9n+9=81 9n=72 n=8

12m + 9n - 4 - 10m + 6n = 2m + 15n - 4

9n + 12y = 3(3n + 4y)

8m-48

11m + 6n - 2m + 9n = 9m + 15n or 3(3m + 5n)

The equation N-10 plus 9N-e equals 10N-3. This is a math problem.

2+3n+2+9n would equal 4+12n after adding all like numbers.